Startup strategies to be applied in the pymes of the Sabana centro - Martínez Albarracín, Carlos; Bolívar-Salgado, William; Segura-Garavito, Mabel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
SMEs in Sabana Centro, Cundinamarca, Colombia, have difficulties to compete in a dynamic market. Therefore, this research aims to define what strategies should be implemented by the entrepreneurs of Sabana Centro, which are currently used by Startups?In order to answer this question, a mixed research is carried out. Methodology: A documentary review is made using databases, implementing statistical tools with a sample of 377 companies in the region. Identifying strategic trends in the use of Startups.